A new method for the size estimation of the RNA genome segments of influenza virus. - Sleigh, M J (1979)
Previous estimates of the size of the RNA genome segments of influenza virus have been unreliable because of a lack of suitable RNA species as size markers. We have attempted to overcome this problem by utilising the ability of AMV reverse transcriptase to synthesise full length DNA copies of RNA molecules in the presence of a suitable primer. By comparing such DNA copies of the RNA segments of the influenza virus genome with sequenced restriction fragments from the E. coli plasmid pBR322, we have made more reliable estimates of the sizes of the eight genome segments from influenza virus A/NT/60/68.